Analysis and prediction of woven fabric design impact on fabric/polymer composite drilling energy. (17th November 2022) - El Messiry, Magdi; Youssef El-Tarfawy, Shaimaa; El Deeb, Rania
Damage, generated during drilling processes, will affect the material integrity and further delamination through the fiber-reinforced composite cross-section. Drilling is necessary for the assembly processes of composite parts. This article deals with the effect of the weave parameters on the drilling mechanism. The mechanism of the yarn shearing ring drilling was investigated, and the quality of the drilled hole was carefully examined for different drilling conditions. Set up for measuring the power consumption during the drilling of different samples as well as the value of the thrust force was constructed. In the drilling of fabric-reinforced polymer composite, the torque, thrust force, and delamination factor are depending directly on fabric design parameters. It was shown that both, drilling power and drilling thrust force, are proportional to the total specific fabric stiffness. Delamination caused by drilling thrust is one of the most problematic defects after drilling laminate composite. A drilling Index was developed and could be used to evaluate the effect of the fabric design of laminate on its composite drilling performance. It was revealed that significantly higher drilling power is needed for the plain weave fabric design than for the other fabric designs of the same unit repeat as well as for the laminates of high fiber volume fraction and high total flexural rigidity. Analysis of the delamination factor and the drilling power showed a high correlation with total fabric flexural rigidity.